Developing and validating a multidimensional Chinese Parental Psychological Control Scale - Zhu, Xiaoqin; Dou, Diya; Pan, Yangu (Frontiers in Psychology, 2023)
This study validated a Chinese Parental Psychological Control Scale (CPPCS) among secondary school students in mainland China. The item pool consisting of 65 items was constructed based on consultation with existing measures and focus group interviews of 19 Chinese adolescents. After content validation conducted by 14 experts, a total of 40 items were retained and subject to further factorial validation based on a sample of 963 Chinese adolescents (mean age = 13.39 ± .72; 52.23% females). Using the two random-split half samples, exploratory and confirmatory factor analyses retained 30 items that loaded on three factors, including “relational induction” (twelve items), “harsh psychological control” (twelve items), and “social comparison shame” (six items). The three-factor structure was invariant across gender (male versus female) and grades (grade 7 versus grade 8) among the whole sample. Cronbach’s αs of the three dimensions in maternal and paternal subscales ranged between .89 and .92, suggesting adequate internal consistency. The three dimensions were significantly correlated with each other, supporting the scale’s convergent validity. The concurrent validity of the CPPCS was supported by the positive correlations between subscales and parental rejection, and the negative correlations between subscales and parental warmth. In addition, while the “harsh psychological control” and “social comparison shame” negatively predicted adolescents’ well-being, “relational induction” positively predicted adolescents’ well-being. The findings suggest that the CPPCS is a promising instrument for measuring multidimensional psychological control among Chinese parents and for investigating and comparing individual dimensions’ effect on adolescents’ development.